Benzenesulfonamides: A Unique Class of Chemokine Receptor Type 4 Inhibitors. Issue 4 (6th March 2013) - Mooring, Suazette Reid; Liu, Jin; Liang, Zhongxing; Ahn, Jeffrey; Hong, Samuel; Yoon, Younghyoun; Snyder, James P.; Shim, Hyunsuk
Abstract The interaction of CXCR4 with CXCL12 (SDF‐1) plays a critical role in cancer metastasis by facilitating the homing of tumor cells to metastatic sites. Based on our previously published work on CXCR4 antagonists, we have synthesized a series of aryl sulfonamides that inhibit the CXCR4/CXCL12 interaction. Analogue bioactivities were assessed with binding affinity and Matrigel invasion assays. Computer modeling was employed to evaluate a selection of the new analogues docked into the CXCR4 X‐ray structure and to rationalize discrepancies between the affinity and Matrigel in vitro assays. A lead compound displays nanomolar potency in the binding affinity assay (IC50=8.0 nM) and the Matrigel invasion assay (100 % blockade of invasion at 10 nM). These data demonstrate that benzenesulfonamides are a unique class of CXCR4 inhibitors with high potency.